Enabling Value Added Scientific Applications of ICESat‐2 Data With Effective Removal of Afterpulses. Issue 6 (8th June 2021) - Lu, Xiaomei; Hu, Yongxiang; Yang, Yuekui; Vaughan, Mark; Palm, Stephen; Trepte, Charles; Omar, Ali; Lucker, Patricia; Baize, Rosemary
Abstract: The Advanced Topographic Laser Altimeter System (ATLAS) aboard the Ice, Cloud, and land Elevation Satellite‐2 (ICESat‐2) has been making very high resolution measurements of the Earth's surface elevation since October 2018. ATLAS uses photomultiplier tubes (PMTs) as detectors in photon counting mode, so that a single photon reflected back to the receiver triggers a detection within the ICESat‐2 data acquisition system. However, one characteristic of ICESat‐2 detected photons is the possible presence of afterpulses, defined as small amplitude pulses occurring after the primary signal pulse due to photon arrival. The disadvantage of these afterpulses is that they often confound the accurate measurements of low level signals following a large amplitude of signal and can degrade energy resolution and cause errors in pulse counting applications. This paper discusses and summarizes the after‐pulsing effects exhibited by the ATLAS PMTs based on on‐orbit measurements over different seasons and geographic regions. The potential impacts of these after‐pulsing effects on altimetry and ocean subsurface retrievals are discussed. Plain Language Summary: After‐pulsing effects occurring in the ICESat‐2 Advanced Topographic Laser Altimeter System (ATLAS) are characterized from the on‐orbit measurements acquired over different surface types. Multiple echoes due to after‐pulsing effects in the ATLAS photomultiplier tubes (PMTs) are clearly seen below the Earth's surface where the signal should be totally attenuated. The afterpulses captured from on‐orbit measurements are caused by three different reasons: (1) the effects of the dead‐time circuit (∼3 ns) due to PMT saturation; (2) the effects of optical reflections within the ATLAS receiver optical components; (3) PMT afterpulses. The echoes separated by ∼0.45 m are attributed to the effect of the dead‐time circuit (∼3 ns) due to PMT saturation. The echoes at ∼2.3 and ∼4.2 m below the primary surface returns are caused by the optical reflections within the ATLAS receiver optical components, while the echoes from ∼10 to ∼45 m away from the primary surface signal are due to the PMT afterpulses with a longer time delay. The ICESat‐2 ATLAS instrument response is derived from both a measurement of the transmitted laser pulse shape and measured photon events arising from land surfaces with different surface albedos. The ICESat‐2 on‐orbit measurements demonstrate that the ATLAS impulse response during different months and over different surface types is essentially identical. Key Points: The effects of after‐pulsing by the Advanced Topographic Laser Altimeter System (ATLAS) aboard the ICESat‐2 satellite are described The transient response of the ATLAS receiver is characterized over different measurement regimes The potential impacts of these detector artifacts on ICESat‐2 science studies are discussed